Sensitivity Analysis of Calibration in the Water Evaluation And Planning (WEAP) Model for Water Resource Management in Keyang, Slahung, Sungkur Watershed - Dianeka, Belia Tatika Arno; Lasminto, Umboro (Institut Teknologi Sepuluh Nopember, 2025)
Water availability becomes an important issue as the population increases due to limited water resources not proportional to the increasing demand. The Keyang, Slahung, and Sungkur sub-watersheds in Ponorogo Regency, East Java, face drought during the dry season and flooding during the wet season. This research aims to analyse water availability by considering irrigation needs and cropping patterns, and provide recommendations for the allocation of water supply from surface water for efficient use in the next 30 years. Water Evaluation And Planning (WEAP) application was used for the analysis, with trial and error method to adjust the parameter values. The optimum parameter values obtained were Z1 = 0, Z2 = 0, DWC = 1000, DC = 100, RRF = 2, RZC = 300, SWC = 1000, and PFD = 0.05. Based on these optimum parameters, the model interpretation of NSE is 0.825 (good category), RMSE 11.923 (good enough category), PBIAS 40.152 (good enough category), R2 (medium influence category), and MAPE 0.873 (very accurate category). This model shows that the simulation results reflect the actual existing conditions.